2003
DOI: 10.1098/rsta.2003.1301
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering: survey of observations and derived principles

Abstract: We review the most salient observations and physical principles of knock-on and electronic sputtering and the role of sputtering in several astrophysical settings and applications in research and technology. In addition, we emphasize some unsolved problems, propose experiments and provide guides to representative literature reviews and significant recent publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 107 publications
1
18
0
Order By: Relevance
“…Experimental kinetic sputtering studies of various oxides, minerals, lunar simulants, and lunar soils have also been reported in Nenadovic et al . [], Baragiola [], and references therein, and Dukes and Baragiolo [], focusing on mass loss measurements, analysis of secondary ion ejection, or ion impact‐induced X‐ray photoelectron spectroscopy (XPS) surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental kinetic sputtering studies of various oxides, minerals, lunar simulants, and lunar soils have also been reported in Nenadovic et al . [], Baragiola [], and references therein, and Dukes and Baragiolo [], focusing on mass loss measurements, analysis of secondary ion ejection, or ion impact‐induced X‐ray photoelectron spectroscopy (XPS) surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…As the energetic ions strike the film surface, two different phenomena take place in the crystal grains, depending on their orientation: ionmilling and ion-channeling. Grains that are randomly-oriented with respect to the ion-beam direction undergo ion-milling and thus are progressively removed from the sample surface [33]. Conversely, those oriented such that their open-most crystal-axis is parallel to the ionbeam undergo ion-channeling and thus survive ion-irradiation [34].…”
Section: Methodsmentioning
confidence: 99%
“…Sputtering is another technique of physical vapor deposition (PVD) in which energetic ion beam bombards the surface of bulk material, displaces the atoms or molecules by energy transfer in the collision, which are then deposited on the substrate [41]. These ions, which ideally should have single charge for all ions, are positively charged and are initially produced from an inert gas.…”
Section: Sputteringmentioning
confidence: 99%